Pengaruh Model Pembelajaran terhadap Hasil Belajar Siswa SMK Otomotif: Meta Analisis - Fatah, Amirrudin; Iskandar, Ranu; Naryanto, Rizqi Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to analyze the effectiveness of various learning models on the learning outcomes of Automotive Vocational High School students through a quantitative meta-analysis approach. Secondary data were obtained from Google Scholar and Garuda using keywords such as "influence of learning models" and "SMK learning outcomes." Of the 75 initial studies, 19 articles met the inclusion criteria and were analyzed using JASP software. Heterogeneity tests showed that the data were heterogeneous (Q=662.658; p<0.001), so the Random Effect model was used. The results showed that the learning model had a significant positive effect on learning outcomes, with a combined effect size of 1.724 (p=0.041). Analysis based on region showed no significant differences, while based on model type, most models such as Discovery Learning and Cooperative significantly decreased effectiveness compared to baseline conditions, except for Project-Based Learning which did not show a significant effect. Although there were indications of publication bias in the funnel plot, the results of the regression and correlation tests did not support consistent asymmetry. These findings indicate that the use of active learning models contributes positively to improving the learning outcomes of Automotive Vocational High School students.